Fluorescence imaging of stained red blood cells with simultaneous resonance Raman photostability analysis. Issue 14 (14th June 2019) - Talib, Ansam J.; Fisher, Andrew; Voronine, Dmitri V.; Sinyukov, Alexander M.; Bustamante Lopez, Sandra C.; Ambardar, Sharad; Meissner, Kenith E.; Scully, Marlan O.; Sokolov, Alexei V.
Abstract : Simultaneous fluorescence and resonance Raman imaging of R6G-stained red blood cells with optimal laser power. Abstract : Optical spectroscopic imaging of biological systems has important applications in medical diagnosis, biochemistry, and image-guided surgery. Vibrational spectroscopy, such as Raman scattering, provides high chemical selectivity but is limited by weak signals and a large fluorescence background. Fluorescence imaging is often used by introducing specific dyes in biological systems to label different system parts and to increase the image contrast. However, the extrinsic fluorescence of the staining molecules often masks the intrinsic vibrational signals of biomolecules, which could also be simultaneously detected using the same excitation laser source. Therefore, fluorescence staining is often accompanied by the loss of other important complimentary information. For example, the high laser power often used for the rapid, high-quality imaging could lead to photo-induced suppression or bleaching of the fluorescence and Raman signals resulting in sample photodamage. Therefore, simultaneous imaging and photodamage analysis need to be performed in a controlled bioimaging experiment. Here we perform simultaneous spectroscopic bioimaging and photostability analysis of rhodamine 6G (R6G) stained red blood cells (RBCs) using both fluorescence and resonance Raman imaging in a single 532 nm laser excitation experiment. We develop a corresponding data processing algorithm which allows separation of the two spectroscopic signals. We control the relative intensity of the R6G and RBC signals by varying the excitation laser power and simultaneously monitor the photostability of RBCs. We observe no significant photodamage of RBCs through the absence of changes in the relative Raman peak intensities. Conversely, the R6G molecules show bleaching with the suppression of both the fluorescence and resonance Raman signals. Our approach may be generalized to other types of stained cells with the appropriate selection of fluorescent dyes and excitation sources.